1989
DOI: 10.1029/jd094id13p16269
|View full text |Cite
|
Sign up to set email alerts
|

Damping of acoustic gravity waves caused by the conductivity of the ionosphere

Abstract: The influence of ionization and conduction on the dispersion of acoustic gravity waves in the upper atmosphere has been investigated by means of an analysis of the corresponding dispersion relation, when the geomagnetic field is directed horizontally. It is shown that we have to distinguish two situations, i.e., acoustic gravity waves propagating perpendicular or nearly perpendicular to the Earth's magnetic field and acoustic gravity waves propagating oblique or parallel to the Earth's magnetic field. This las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As the observed waves only have two or three cycles, the AGW under consideration causes a temperature increase of about 40~ The presence of AGW will also affect the ionization rate due to the change of the electron density (Yeh and Liu, 1974;Nagorskiy, 1985). The coupling between AGW and electromagnetic waves was theoretically analyzed by Raemer (1972), Krechetov (1988), and Miesen et al (1989). In the term F of Equation (lb) the Lorentz force J • B is now included where the current density is given by…”
Section: M9mentioning
confidence: 99%
See 1 more Smart Citation
“…As the observed waves only have two or three cycles, the AGW under consideration causes a temperature increase of about 40~ The presence of AGW will also affect the ionization rate due to the change of the electron density (Yeh and Liu, 1974;Nagorskiy, 1985). The coupling between AGW and electromagnetic waves was theoretically analyzed by Raemer (1972), Krechetov (1988), and Miesen et al (1989). In the term F of Equation (lb) the Lorentz force J • B is now included where the current density is given by…”
Section: M9mentioning
confidence: 99%
“…Miesen et al (1989) have shown that for AGW propagating perpendicular to the Earth's magnetic field this effect is not negligible.…”
Section: M9mentioning
confidence: 99%
“…This consideration can be simplified, if only the geomagnetic influence on the GW propagation is of primary interest. Hines (), Miesen et al (), and Miesen () reported that, for typical ionospheric conductivities, the electromagnetic and hydrodynamic parts are weakly coupled in the sense that the induced variations of the electromagnetic field weakly affect the hydrodynamic variables. Therefore, terms containing boldE and boldB can be neglected, and only the dynamo‐part term boldv×boldB0×boldB0 is retained in .…”
Section: Interaction Of Ions and Neutrals In Gravity Wave Motionsmentioning
confidence: 99%
“…TIDs are routinely observed in the ionosphere, especially by incoherent scatter radars, and their relationship to GWs have been studied by a number of authors (e.g., Hocke & Schlegel, 1996;Kirchengast, 1997). The main theoretical results concerning the influence of ion drag on acoustic-gravity waves have been obtained in the works of Hines (1955), Liu and Yeh (1969), and Hines and Hooke (1970), and further extended in the papers of Francis (1973), Hickey and Cole (1987), Miesen et al (1989), and Miesen (1991). They derived dispersion relations of various complexities for acoustic-gravity waves in the presence of ion drag and magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The electron density perturbation is related to the plasma velocity perturbation through the first-order electron (or ion) continuity equation, which in the absence of strong plasma density gradients is [Klostermeyer, 1978] Nel k. Uil the present calculation since it corresponds, at least in the windless case, to damping by ion drag, which has been treated by different methods in previous literature [see Gossard and Hooke, 1975;DuBroff et al, 1977;Miesen et al, 1989]. Second, the large, steady convection flow limit is examined in section 4.2, and finally, the effects of critical coupling between waves and the plasma flow on internal gravity wave stability is briefly commented on in section 4.3.…”
Section: In Convecting Plasmamentioning
confidence: 99%